A case of Bickerstaff brainstem encephalitis and acute lymphoblastic leukaemia - Hashim, Hasriza; Sulaiman Sahari, Narisa; Mohd Sazlly Lim, Sazlyna; Hasan, Shariful; Hoo, Fan Kee (Lahore Medical & Dental College, 2014)
Bickerstaff Brainstem Encephalitis (BBE) is a post-infectious immune disorder. It is rare, yet the most severe variant of Guillain-Barre Syndrome (GBS) in terms of initial presentation. Moreover, the coexistence of BBE and Acute Lymphoblastic Leukaemia (ALL) is distinctly uncommon. We report a case of a patient with a background history of Precursor B cell Acute Lymphoblastic Leukaemia (pre B ALL) presented with a mixture of peripheral and central nervous system involvement with cortical, subcortical and cerebellar lesions on brain magnetic resonance imaging (MRI), and was eventually diagnosed with BBE. In this case, we illustrate the complexity in diagnosing BBE, a rare variant of GBS due to atypical presentation.